A Visual Narrative: Leveraging Digital Comics To Preserve And Promote Traditional Arts - Angkawijaya, Yongkie; Kusumawati, Yudhistya Ayu; Gozali, Alya; Yana, Erlyana (Jurnal Bahasa Rupa, 2024)
Digital media and emerging technological tools are expanding the reach of various practices, including art, which increasingly takes abstract, visual, or musical forms. This transformation has led to a growing detachment from traditional art forms, contributing to their diminishing appeal. Furthermore, regional cultural institutions, such as art galleries, often struggle to effectively promote traditional arts, exacerbating the challenges of preserving and revitalizing these cultural expressions in the face of rapid societal change. This research explores the innovative intersection of digital comics and traditional arts as a means of cultural preservation and promotion. This research investigates how the storytelling power of comics, with its engaging visuals and narrative structure, can be harnessed to communicate the richness of traditional art forms to a broader, more diverse audience. By integrating elements of traditional culture into digital comic formats, the study seeks to bridge generational and cultural gaps, ensuring that the cultural significance of traditional arts is not only preserved but also made relevant in today’s digital-centric world. The research emphasizes how this hybrid medium can serve as an accessible platform for education, engagement, and cultural exchange, providing an interactive way to showcase traditional art techniques, history, and symbolism. Furthermore, the study examines the potential of digital comics to expand the reach and visibility of traditional art, particularly among younger generations who may be less engaged with conventional art forms. Through an analysis of case studies and the development of prototype digital comic projects, the research highlights the effectiveness of combining modern digital tools with the timeless appeal of visual storytelling. The study suggests that by leveraging the popularity of comics and graphic novels, traditional art can be introduced in a fresh, dynamic way, fostering greater appreciation and understanding. This research ultimately proposes a new model for preserving cultural heritage, blending creativity, technology, and tradition to create compelling narratives that resonate with a contemporary audience.